Anti IL-17 in psoriasis. (2nd November 2019) - Ly, Karen; Smith, Mary P.; Thibodeaux, Quinn; Reddy, Vidhatha; Liao, Wilson; Bhutani, Tina
ABSTRACT: Introduction : Psoriasis is a chronic, immune-mediated disease with significant associated comorbidities. Its pathogenesis is likely multifactorial, however, the interleukin-23/T helper 17 pathway has been identified as a critical axis in its pathogenesis. Interleukin-17A is the primary effector of this pathway and overexpression of IL-17A results in epidermal hyperplasia and an overly robust inflammatory response, resulting in the skin plaques and systemic inflammation seen in psoriasis. Targeted anti IL-17 therapies have demonstrated efficacy in the treatment of moderate-to-severe plaque psoriasis. Areas covered : A PubMed search was conducted for relevant literature. Secukinumab, ixekizumab, and brodalumab are anti IL-17 inhibitors currently approved for the treatment of moderate-to-severe plaque psoriasis. The efficacy and safety data from key phase III clinical trials are reviewed here. Expert opinion : By targeting a key mediator of the interleukin-23/T helper 17 pathway, IL-17 antagonists are an effective treatment for plaque psoriasis. It has demonstrated efficacy and a favorable safety profile in key phase III clinical trials. In addition to efficacy, IL-17 antagonists have also shown long-term maintenance of treatment response and a quick onset of action. The efficacy of IL-17 inhibitors in the treatment of moderate-to-severe psoriasis underscores the importance of the IL-23/Th17 pathway in the pathogenesis of psoriasis.